The present-day geothermal regime of the North Jiangsu Basin, East China. (November 2020) - Wang, Yibo; Wang, Lijuan; Hu, Di; Guan, Junpeng; Bai, Yang; Wang, Zhuting; Jiang, Guangzheng; Hu, Jie; Tang, Boning; Zhu, Chuanqing; Hu, Shengbiao
Highlights: Borehole temperature logs, the thermal parameters and 71 high-quality heat-flow values were reported. The whole thermal conductivity column of the strata and rocks in different geologic age in the NJB were first established. The two-dimensional temperature distribution characteristics of the NJB were simulated and discussed. The causes of the distribution pattern and geodynamic implications of these heat-flow data were discussed. Abstract: Heat flow and thermal state complement seismic information and provide strong constraints on the thickness, geophysical properties, and tectonic evolution of the lithosphere. The North Jiangsu Basin (NJB) is located in the Lower Yangtze Craton as a wedge block of ancient plate boundary-adjacent to the southeast corner of the North China Craton experienced destruction in the Late Mesozoic, and it is of great interest to learn the geothermal characteristics of the basin. We present 71 new heat flow measurements derived from temperature logs and detailed thermal conductivity measurements of 189 dry core samples and 24 outcrop samples. We analyze these new data in combination with published data to plot the temperature gradient and heat flow distribution maps. The results show that: (1) temperature gradient values in the NJB are in the 21.5–59.2 °C km −1 range, with a mean value of 30.2 ± 6.5 °C km −1 ; (2) heat flow values are in the 45.7–109.7 mW m −2 range, with a mean value of 67.9 ± 7.7 mW m −2 ; (3) the highest temperature gradient and heat flow value is located in or around the Jianhu Uplift, and thermal refraction is the leading cause; and (4) the destruction of the North China Craton at the end of the Late Mesozoic was likely to affect the NJB, and the unified deep dynamic mechanism makes the NJB and the Bohai Bay Basin now in a similar thermal state.